Development of highly stable Ni-doped zeolitic imidazole framework (ZIF-67) based catalyst for CO2 methanation reaction - Aldoghachi, Ali; Yun Hin, Taufiq-Yap; Saiman, Mohd Izham; Voon, Lee Hwei; Zheng, Alvin Lim Teik; Seenivasagam, Sivasangar (Elsevier, 2024)
The conversion of CO2 into synthetic natural gas via methanation reaction has been gaining more attention. The development of active and stable catalysts at relatively low reaction temperatures is a critical issue to be addressed. Highly porous metal-organic framework (MOF) material, ZIF-67 doped with 1–12 wt% of nickel, was prepared via the wet-impregnation method. The catalytic test was started with in situ reductions of 0.05 g of catalyst. The reaction was performed at the temperature range of 200–400 °C, with a flow rate of 108,000 mL g−1 h−1 using a feed gas mixture (CO2:H2:N2) in a 1:4:5 ratio. Physicochemical characterisation showed that a highly porous and uniformly dispersed Ni-added ZIF-67-based catalyst was obtained and exhibited excellent catalytic activity in CO2 conversion. Preliminary catalytic testing showed that the 8 wt% ZIF-67 catalyst was very active in methanation reactions, with CO2 conversion of ∼56 % and CH4 selectivity of ∼96 % at 300 °C. Furthermore, the catalyst was very stable and maintained high catalytic activity (conversion ∼53 %, selectivity ∼94 %) without any sign of deactivation for 500 h of methanation reaction. Hence, the MOF-based Ni/ZIF-67 catalyst showed excellent potential to be explored as an effective methanation catalyst, and further investigation of the reaction parameters could lead to exceptional catalytic performance.